KONSEP KAJIAN KONTEMPORER MANUSIA DI DALAM AL QUR'AN - Novia Lisliningsih; Tuti Kurnia; Wedra Aprison (CV. Adiba Aisha Amira, 2023)
Concepts and studies about humans are explained based on the concepts outlined in the Word of Allah in the Qur'an. Apart from that, humans also experience an educational process, where the focal point of discussion is Islamic religious education. Apart from that, humans also have clear concepts in PAI. There are clearly several words that are interpreted as humans in the Qur'an, namely Al Insan, An naas, Al Basyar and Bani Adam. Each word has its own meaning and is even repeated several times in the Qur'an. Every time changes, humans are always involved in it. With the implementation of an independent curriculum, humans have an important role in implementing and developing it. The research method used in this article is to use the library method, namely reading various journals and books, collecting literature and storing it in other information sources in the library to obtain a good and correct understanding of Islamic education material as well as getting to know the Independent Curriculum theory.